The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bcr-2018-224873
|View full text |Cite
|
Sign up to set email alerts
|

When a patient with depression is feeling sleepy, be aware of sleep apnoea

Abstract: A 67-year-old man was referred to an outpatient clinic of geriatric psychiatry because of persistent symptoms of depression and anxiety, accompanied by sleepiness. The latter had been evaluated multiple times in the general practice over several years; each time it was considered to be a symptom of depression. After referral, the patient was diagnosed with severe obstructive sleep apnoea (OSA), comorbid to a depressive and anxiety disorder. Retrospectively, we conclude that affective symptoms accompanying OSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is also possible to correlate physical depression with physical symptoms. Fatigue or low energy, disturbed sleeping, particularly waking early in the morning, especially headaches, treatment Feeling or appearing to be slowed or irritated [9]. Treatment of this antidepressant, antipsychotic drug, antihypertensive, anticonvulsant antipsychotics, benzodiazepine and antianxiety along with this psychotherapy is most important such as speaking therapy, Light therapy, alternative therapies, exercise, medication, yoga [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to correlate physical depression with physical symptoms. Fatigue or low energy, disturbed sleeping, particularly waking early in the morning, especially headaches, treatment Feeling or appearing to be slowed or irritated [9]. Treatment of this antidepressant, antipsychotic drug, antihypertensive, anticonvulsant antipsychotics, benzodiazepine and antianxiety along with this psychotherapy is most important such as speaking therapy, Light therapy, alternative therapies, exercise, medication, yoga [10].…”
Section: Introductionmentioning
confidence: 99%
“…a previous study reported a higher anxiety dream incidence in OSA patients (Carrasco et al, 2006) and OSA-related snoring when compared to controls (de Groen et al, 1993). OSA also appears to confer a higher risk for future development of nocturnal panic attacks due to breathing-related OSA symptoms (Edlund et al, 1991;, as well as somatic symptoms of anxiety such as excessive sweating, or nightmares (Wiersema et al, 2018). In light of these findings, it can be assumed that anxiety as measured in our study may be associated with psychophysiological symptomatology related to panic attacks, rather than with anxiety in general.…”
Section: Night-time Sleep Quality and Work Functioning: The Moderatinmentioning
confidence: 57%
“…Neuroimaging techniques also showed that loneliness may consequently lead to an increased level of hypervigilance to hostile cues and a negative attitude towards others (Cacioppo et al, 2016). Moreover, higher levels of anxiety or hostility identified in OSA patients Wiersema et al, 2018) may be associated with a lack of ability to communicate with others (Perfect et al, 2013), social inhibition, social dysfunction , and oppositional orientation towards others . Thus, it may be assumed that patients with OSA, identified as hostility-prone, may have even poorer motivation to participate in social activities.…”
Section: Social Support and Suicidal Ideationmentioning
confidence: 99%